The assessment of standard concrete under damage and undamage condition using non-destructive test (NDT) method - Irianto, Nur Ain Izzati; Mohd Khirul Anwar, Balqis Auji; Khairul Anuar, Izz Zabur (Multidisciplinary Applied Research and Innovation, 2023)
Destructive testing on specimens taken during the building of structural elements, are currently the most prevalent method for controlling the quality of concrete on-site. In concrete works, the most common NDT method used are Penetration method, rebound hammer method, Pull out test method and Radioactive methods. Previously, studies on concrete strength were based solely on compressive strength obtained from machines in damaged conditions.[2] The main objectives of this study is to Determine compressive strength of standard concrete using Design of Experiment (DOE) Method and to Analyse the impurity of standard concrete under undamaged condition using UPV. This study will adhere to a conventional procedure in accordance with British Standard concreting procedures This study will also employ the Design of Experiment (DOE) method. Materials such as cement, water, and aggregates are required in the production of concrete sample. Curing processes of 7,14 and 28 days were used to maintain moisture in the concrete and this initiative will take place on the campus of UTHM Pagoh. From this study, it is expected that the compressive strength are directly affected by the curing days, and the UPV test result will remain constant as the impurity of the concrete were determined by the quality controls during the concreting process.[11] To achieve the study’s goals, all of the data gathered from the sample testing were analysed and debated. To ensure the accuracy of the data, it was advised that all normal operating procedures be followed.